2019
DOI: 10.2147/iprp.s162799
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pharmacy student professional identity formation: a scoping review</p>

Abstract: Purpose Transitioning from being pharmacy students to pharmacists is challenging. Students need to reconcile their professional aspirations and what they have learnt with the realities of practice. A smooth transition can be hampered when they are unable to enact the role they have envisaged or if their expectations are not met. These challenges relate to professional identity. A key challenge for pharmacy educators is how best to support the professional identity formation (PIF) of pharmacy stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 53 publications
0
90
0
Order By: Relevance
“…Because the education results in a vocational degree, it is essential for the students to be prepared, and for the university to prepare the students, for their professional working life. In addition, it is important for the students to be able to develop their professional identity to facilitate the transition from pharmacy student to pharmacist [ 7 , 18 ]. The master’s graduates generally felt more prepared to work as pharmacists compared with the bachelor’s graduates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the education results in a vocational degree, it is essential for the students to be prepared, and for the university to prepare the students, for their professional working life. In addition, it is important for the students to be able to develop their professional identity to facilitate the transition from pharmacy student to pharmacist [ 7 , 18 ]. The master’s graduates generally felt more prepared to work as pharmacists compared with the bachelor’s graduates.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Canada showed that community pharmacists lack a clear professional identity, and this may affect pharmacists´ interactions with other healthcare personnel or patients [ 7 ]. Another study concluded that pharmacy students experienced challenges when forming their professional identity and supporting the formation of a professional identity is an important goal for pharmacy education [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of these curricular elements play a valuable role in enhanced professional identity formation, but perhaps the most important is the expansion in experiential education. As pointed out by Noble et al, 6 students “need to reconcile their curricular learnings and aspirations for professional practice with the realities of authentic practice.” Early experiences are critical in that a negative experience can be a significant setback in a student’s tenuous formation of professional identity. Importantly, early experiences are interspersed in the didactic curriculum.…”
mentioning
confidence: 99%
“…25 Interestingly, our students reflected on all 10 of these traits, with varying degrees of emphasis, as per our distillation of reflection content into six overarching themes. While we recognize that the white coat ceremony is one small component of student professional development, 26 our findings suggest that participation in the white coat ceremony serves as a powerful way to introduce student professionalization early in the professional education journey, with many important professional themes surfacing as revealed by our thematic analysis.…”
Section: Discussionmentioning
confidence: 62%
“…The actual cloaking by a faculty member who was also wearing a white coat represented to students that these faculty members, who often were cited by name in reflections, were professional role models to the students. Such positive role modeling is essential to the development of strong professional identities, 26 and the white coat ceremony served as foundational in this regard. Further, students viewed the cloaking faculty members as gatekeepers to the profession of pharmacy, and these gatekeepers were now welcoming them in.…”
Section: Discussionmentioning
confidence: 99%